Insect-resistant cowpea in Nigeria: An ex ante economic assessment of a crop improvement initiative - Phillip, Dayo; Nin-Pratt, Alejandro; Zambrano, Patricia; Wood-Sichra, Ulrike; Kato, Edward; Komen, John; Hanson, Hillary; Falck-Zepeda, José B.; Chambers, Judith A. (International Food Policy Research Institute, 2019)
Since oil prices’ decline in 2014, agriculture has received renewed interest in Nigeria as a key sector for achieving sustainable growth and generating foreign exchange. One of the identified obstacles to achieving these goals is the need to improve agricultural productivity. Cowpea is one of the priority crops identified for productivity improvement. Currently cowpea yields are below 900 kg/ha, but it has been shown that with the right technology, these yields could potentially double. One of the main biotic constraints for cowpea is the infestation of the insect pod borer (Maruca Vitrata). No conventional variety has been developed to resist this pest, but with the use of biotechnology and the sustained collaboration of national and international partners over many years, there is now a genetically modified pod-borer-resistant (or more generally insect-resistant) cowpea. This paper estimates the potential economic benefits of adopting this new technology and the cost that Nigeria will incur if this adoption is delayed. The analysis is conducted using an economic surplus partial equilibrium model run with the newly developed DREAMpy software, data drawn from the Nigeria General Household Survey 2015–2016, estimations using these data, and other local sources. The estimations show that if the insect-resistant cowpea is planted in 2020, the net present-value benefits for producers and consumers would be around US$350 million, 70 percent of which would be accrued by producers. The distribution of benefits by region show that Sudan-Sahel will accrue the most benefits, given the relative concentration of cowpea in this region and the estimated higher adoption rates and yield changes. Almost half of producers’ total benefit will go to large producers, who represent only 20 percent of all cowpea producers, while small producers, representing half of all cowpea producers, will receive 24 percent of the benefit. Additionally, the analysis shows that a five-year regulatory delay will decrease the estimated benefits by around 35 percent. While Nigeria already has in place a competent biosafety system that will most likely ensure that these regulatory delays will not materialize, these estimations highlight the importance of having an evidence-based, efficient, predictable, and transparent regulatory system to ensure that the expected economic benefits are realized.